Perilaku Konsumtif Mahasiswa Berbelanja di E-Commerce Shopee pada Masa Pandemi Dalam Perspektif Gender: Studi Kasus Mahasiswa Prodi Ekonomi Islam Uinsu - Siregar, Ridha Maysaroh; Susanti, Neila; Aslami, Nuri (Ikatan Da'i Indonesia, 2023)
This study aims to describe the consumer behavior of online shopping students from a gender perspective during the pandemic. This study uses a qualitative approach, which focuses more on the description and description of a phenomenon that occurs. The method of taking research subjects using purposive sampling, while the data collection techniques are interviews and documentation. The results obtained from this study indicate that female and male consumers perceive the convenience and efficiency obtained when shopping through e-commerce which actually encourages them to have consumptive behavior in the midst of a pandemic. Their perspective is through shopping activities in the midst of a pandemic, such as women spending more time doing online shopping activities than men. Women like to open online shopping applications without the purpose of buying but only looking at the various promos and items available in them. In addition to promos, more affordable prices and practicality are one of the reasons women do shopping activities in e-commerce. For the sake of maintaining self appearance and getting pleasure with the types of items that are most often purchased are fashion, skincare and bodycare. It is different from men who think that opening an e-commerce like shopee has a purpose, namely to buy goods that have been planned. Men are also more likely to buy fashion products in the midst of a pandemic. Various models, trends and practicality are one of the reasons men make purchases in e-commerce. Items that are often purchased by women and men, especially students of the Islamic Economics Study Program, UIN North Sumatra, are not items that are actually needed in the midst of a pandemic. Their perspective regarding shopping through e-commerce actually plunges students into consumptive behavior where purchases are made without consideration or irrationality.